Terapia ocupacional e mundo rural: uma revisão de escopo - Silva, Mateus Francisco da (Universidade Federal de São Carlos, 2022)
The rural world is a territory with contexts, histories, and meanings of extreme importance to society as a whole. However, it is still seen as something separate from it and, at the same time, marginalized in relation to the urban environment. In the Brazilian context, it is often seen as a backward, outdated, and rustic space in relation to the urban environment. This space suffers from a lack of public policies and from the conflicts involving land concentration that have characterized the rural world in Brazil since the colonial period. The lack of access to social goods ends up limiting the perspectives of the person who lives there, conforming him to cultural roles built on the basis of this historical process of marginalization, which reduces his autonomy and choices regarding his own life. Taking the global and also the national sphere, the area of Occupational Therapy has carried out works in several of its subareas, in an attempt to contribute to the resolution of problems that involve contexts and subjects that occupy and live in this environment. Thus, the primary objective of this study was to carry out a scope review that encompassed national and foreign productions, seeking to understand, systematize and divulge the scientific production in the interface of occupational therapy with the rural world, analyzing it critically, in order to perceive the potentialities and weaknesses of the production of knowledge and practices in this field, considering the diverse ruralities and contexts worldwide. Results from the five continents were found with data needed to carry out a systematization and a synthesis of this knowledge. These were studied, analyzed, and distributed into six categories according to the issues addressed. We conclude that several studies on the interface between occupational therapy and the rural world have been carried out around the world, addressing various aspects and spheres, both in the scope of practice, including the professionals themselves and the populations assisted, and in the academic environment.
Occupational therapy and rural environment: a scoping review
Keywords: Terapia ocupacional; Rural; Ruralidade; Revisão; Occupational therapy; Rural; Rurality; Review; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL